Phytochemical Screening and Antibacterial Activity of Dendrobium from Papua Against Eschericia coli and Staphylococcus aureus - Supeni Sufaati; Verena Agustini; Agnes E. Maryuni; Eva S. Simaremare (Jurusan Biologi FMIPA Universitas Cenderawasih, 2021)
Orchid found as one of medicinal plant in some areas, especially Dendrobium. Some species were investigated its bioactive compound, and antibacterial activity, but the information about antibacterial activity of Papuan Dendrobium species is still limited. The aims of this research were to determine the phytochemical constituents and the antibacterial activity of ethanolic extract and fraction of Dendrobium species from Papua against Escherichia coli and Staphylococcus aureus. There were three species of Dendrobium namely: D. spectabile, D. violaceoflavens, and D. antennatum used in this study. Dried simplisia was macerated using ethanol, then tested for the phytochemical content. Total ethanolic extract was fractionated with three different solvents, ethanol, ethyl acetate and hexane. Disc diffusion assay was used to examine the antibacterial activities of the total extract and the fractions. Total extract were positive for flavonoid, alkaloid and tanin, except D. spectabile stem extract only alkaloid and tannin. No saponin was found in the plants. The ethyl acetate fraction of leaves of D. spectabile showed the highest antibacterial activity against S. aureus with diameter of inhibition zone 20.54 + 1.47 mm (strong category). Other plant extract and fraction tested had moderate antibacterial activities against both E.coli and S aureus with diameter zone 6-9 mm. The present work indicates that the ethyl acetate fraction of D. spectabile leaves is potential to be developed in antibacterial drug design research. Key words: antibacterial activity; Papua; Dendrobium; E. coli; S. aureus.